1979
DOI: 10.2135/cropsci1979.0011183x001900040015x
|View full text |Cite
|
Sign up to set email alerts
|

Capacity for Proline Accumulation During Water Stress in Barley and Its Implications for Breeding for Drought Resistance1

Abstract: During controlled water stress applied at the threeleaf stage, the barley (Hordeum vulgare L.) cultivars ‘Proctor’ and ‘Excelsior’ showed different rates of free proline accumulation and leaf‐firing. Both processes were faster in Proctor (a drought‐susceptible cultivar) than in Excelsior (a drought‐resistant cultivar). The different rates of proline accumulation during stress in Proctor, in Excelsior, and in a wild barley (H. spontaneum C. Koch) could be attributed to differences in the rate of decline of leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
2

Year Published

1980
1980
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(57 citation statements)
references
References 0 publications
6
49
0
2
Order By: Relevance
“…66). The rapid consumption of proline after rewatering has been observed in a number of crops (Singb, Aspinall & Paleg, 1972;Sivaramakrishnan et al, 1988), but not in dead tissue (Hanson et al, 1979). It therefore appears that although the leaves in treatment D8 in this experiment were partly damaged, having scorched tips and damaged membranes (see above), the unscorched parts of the laminae were able to recover very rapidly.…”
Section: Recovery From Droughtsupporting
confidence: 54%
See 1 more Smart Citation
“…66). The rapid consumption of proline after rewatering has been observed in a number of crops (Singb, Aspinall & Paleg, 1972;Sivaramakrishnan et al, 1988), but not in dead tissue (Hanson et al, 1979). It therefore appears that although the leaves in treatment D8 in this experiment were partly damaged, having scorched tips and damaged membranes (see above), the unscorched parts of the laminae were able to recover very rapidly.…”
Section: Recovery From Droughtsupporting
confidence: 54%
“…Tbis is supported by the observations of Kemble & McPherson (1954) that perennial ryegrass produced proline when wiited during simulated haymaking; of Sivaramakrishnan et al (1988) that sorghum accumulated proline in leaves when extension growth had ceased and i//^. fell below -2 5 MPa; and of Hanson et al (1979) that proline accumulated only in scorched tissues. In an earlier experiment on these populations (Thomas, 1990), the greater accumulation of proline in leaf blades (an average of 101 /imol g^^,, compared with 31 m easured here) was probably a consequence of the artificial drought technique, which involved adding frequent small volumes of water and resulted in a series of short droughts.…”
Section: Adaptation To Droughtmentioning
confidence: 74%
“…Hanson et al (1979), working with Hordeum vulgare L., suggested that proline accumulation was of no practical use in breeding, even though they found a heritable component to this trait. Ceh et al (2009) found no correlation between proline content and drought-resistance in hops (Humulus lupulus L.) and Ilahi and Dorffling (1982) found that drought-susceptible cultivars of Zea mays had higher proline contents that drought-resistant ones.…”
Section: Discussionmentioning
confidence: 99%
“…Proline was extracted from 0.1 g freeze-dried seedlings and spectrophotometrically determined using the acid ninhydrin method described by Hanson et al (1979). To analyze SOD activity, fine powder of seedlings was resuspended in 50 mM potassium phosphate (pH 7.8) containing 0.1 mM EDTA and 1% PVP, and then centrifuged at 12,000 g for 15 min at 4°C.…”
Section: Measurements Of Proline Content and Sod Activitymentioning
confidence: 99%